Implementasi pengelolaan rekod di fakultas teknik universitas Indonesia (FT UI) - Dyah Puspitasari Sri Rahayu (Al Maktabah, 2016)
In carrying out its activities, the organization will produce substantive and facilitatice records.Those records created by the organization must be managed properly to be easily used and retrievedby the organization as the evidence of the organization’s activities. This study aims to determinethe implementation of records management run by Technology Faculty at University of Indonesia.Qualitative method is the approach in this research method with interviewing informants to getthe valid data. The finding of the research is the management of records in Technology Faculty isdecentralized under the responsibility of each unit in Faculty. In managing the records, each unitshave different ways to manage. The principle of record managemnet, they are easy to retrieve, whenthey are needed and requested.